¿How to think the body apart from the idea of a corporeal subject? ‘Mere presence’ and ‘clearance of being’ in ‘Zollikoner Seminare’ de Heidegger - Johnson, Felipe (Anales del Seminario de Historia de la Filosofía, 2020)
This paper aims to discuss the difficulties involved in thinking of us as corporeal beings. Guide for these reflections are Heidegger’s indications on human corporeality made in Zollikoner Seminare. These seminars warn that the current experience of our own body, despite being able to be considered as an immediate one, is rather mediated by our own epochal assumptions and it is already rooted in Western ontological thinking. Thus, this paper attempts to examine the philosophical aporias of such historic-epochal mediation, by exposing Heidegger’s reflections on body from the clearance of being (Lichtung) as a response to the traditional idea of ​​subjectivity founded in the notion of “mere presence” (Vorhandenheit).